Transforming Mathematical Communication: The Effectiveness of RADEC Learning Model in Elementary Education - Sakristi, Maria Putri; Relmasira, Stefanus Christian (Journal of Innovation and Research in Primary Education, 2025)
Mathematical communication skills represent fundamental competencies essential for mathematical literacy development, yet elementary students frequently demonstrate passive engagement in mathematical discourse due to traditional instructional approaches that limit collaborative interaction and communication skill development. This quasi-experimental study employed a pretest-posttest non-equivalent control group design to investigate the effectiveness of the RADEC (Read, Answer, Discuss, Explain, Create) learning model in enhancing mathematical communication skills among elementary students. Participants comprised 51 third-grade students from SD Negeri Gendongan 01 Salatiga, with 27 students in the experimental group receiving RADEC instruction and 24 students in the control group receiving conventional mathematics instruction. Data were collected through validated essay-based assessments measuring written text, drawing, and mathematical expression competencies, supplemented by observations and interviews. Statistical analysis employed Independent Sample T-Tests using SPSS version 27. The experimental group achieved significantly superior performance with a mean score of 80.56 compared to the control group's mean score of 63.83 (p = 0.015, t = -2.534). Performance distribution analysis revealed 63% of experimental students attained very high achievement levels versus 50% in the control group, while low-performing students decreased from 13% to 4% following RADEC implementation.  The RADEC model's systematic progression through Read, Answer, Discuss, Explain, and Create phases effectively develops mathematical communication competencies by facilitating active engagement with mathematical language, collaborative discourse, and creative representation generation. These findings support theoretical frameworks emphasizing mathematical communication as a fundamental process skill essential for mathematical literacy development and provide empirical evidence for student-centered pedagogical approaches in elementary mathematics education.